Improving Service Quality and Knowledge Sharing to Build Sustainable Learning Organizations - Alaa Abdulsalam Mustafa (Global Scientific Publishing, 2024)
Knowledge sharing is one of the processes of knowledge management in organizations. Indeed, it is one of the fundamental processes that leads to the dissemination and transfer of knowledge among individuals working in organizations, and between organizations and other organizations in their environment. The importance of this process appears through the positive results it leads to that contribute in a significant way. Significant in future planning activities and addressing functional problems faced by the organization as it seeks to achieve its goals
Keywords: Service quality; knowledge sharing; sustainable learning organizations